Inteligência artificial no ambiente organizacional: a ótica dos empregados da Terracap - Silva Júnior, Calmon Borges da (2024)
Artificial Intelligence demonstrates the capability of technology to interpret and learn from data adaptively to achieve specific objectives. In the workplace, the application of this technology tends to enhance organizational performance, making it essential to understand how employees perceive it, as they will be the primary users of this innovation. In this context, the TERRACAP organization, the locus of this research, emerges as a public company located in the Federal District, responsible for managing land and real estate businesses in the region. This study was motivated by the growing use of AI in public institutions, where greater efficiency, transparency, and agility are observed. Aligning with these trends, TERRACAP included the strategic goal of "Promoting Integrated Technological Solutions" in its Strategic Planning, emphasizing the adoption of AI as a critical measure to improve processes and services. Based on this premise, the research aims to address the following question: what is the perception of TERRACAP employees regarding the application of Artificial Intelligence in the workplace? The primary objective is to analyze employees' perceptions of the application of AI in TERRACAP's work environment. This exploratory-descriptive research adopts a quantitative approach, utilizing a questionnaire on Attitudes Toward the Application of Artificial Intelligence at Work. The instrument comprises 25 questions distributed across six dimensions: 1) Perceived Human Similarity of Artificial Intelligence; 2) Perceived Adaptability of Artificial Intelligence; 3) Perceived Quality of Artificial Intelligence; 4) Anxiety about Using Artificial Intelligence; 5) Job Insecurity; and 6) Personal Usefulness of Artificial Intelligence. For data analysis, statistical techniques were applied to validate the indicators (dimensions), including Cronbach's Alpha for reliability, Kaiser-Meyer-Olkin for unidimensionality, and Pearson's correlation coefficient with p-value for validity. Additionally, measures of Mean, Standard Deviation, and a 95% Confidence Interval were employed to evaluate the results. The research involved 69 participants out of a population of 76 employees. Respondents work at the strategic (14.49%), tactical (42.03%), and operational (43.48%) levels, with most being permanent employees (56.52%) with up to 20 years of service (85.51%). The predominant age group is up to 50 years old (82.61%), with respondents identifying as male (59.42%) and female (37.68%). The results indicate that AI is not perceived as human-like (dimension 1), but it demonstrates adaptability (dimension 2) and provides quality information (dimension 3), even though it is not always up-to-date (assertion 13). From a personal perspective, AI is considered useful (dimension 6), although it does not necessarily foster a sense of fulfillment at work (assertion 23). Furthermore, significant levels of anxiety about using AI (dimension 4) or job insecurity (dimension 5) were not observed. Finally, applying this study to private organizations is suggested for future research.